Financial Attention and Household Consumption Upgrading - Han Li; Rui Zhang (International Journal of Financial Studies)
Based on data from the China Household Finance Survey (CHFS) conducted in 2019, this paper conducted an in-depth study on the impact and mechanism of financial attention on household consumption upgrading. The study found that an increase in financial attention can help to promote household consumption upgrading, and the result was still robust after using the instrumental variable method and substituting the explained variables. The mechanism analysis showed that financial attention can affect household consumption upgrading by influencing credit constraint and risk sharing. Heterogeneity analysis showed that the promotion effect of financial attention on consumption upgrading was significant in middle- and high-income households, high-financial-literacy households, and households living in first-tier cities.